2011
DOI: 10.2139/ssrn.1739282
|View full text |Cite
|
Sign up to set email alerts
|

Deception in Speeches of Candidates for Public Office

Abstract: The contribution of this article is twofold: the adaptation and application of models of deception from psychology, combined with data-mining techniques, to the text of speeches given by candidates in the 2008 U.S. presidential election; and the observation of both short-term andmedium-term differences in the levels of deception. Rather than considering the effect of deception on voters, deception is used as a lens through which to observe the self-perceptions of candidates and campaigns. The method of analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several studies have revealed the linguistic styles used by politicians that recommend the conservative and liberal's difference in using the emotional language and multi syllabic words (Slatcher et al, 2007;Wojcik et al, 2015). Skillicorn (2015) studied the political deception done by language for the successful accomplishment in the political market. For this purpose, they must appeal to the massive audience regarding the policy issues.…”
Section: Political Languagementioning
confidence: 99%
“…Several studies have revealed the linguistic styles used by politicians that recommend the conservative and liberal's difference in using the emotional language and multi syllabic words (Slatcher et al, 2007;Wojcik et al, 2015). Skillicorn (2015) studied the political deception done by language for the successful accomplishment in the political market. For this purpose, they must appeal to the massive audience regarding the policy issues.…”
Section: Political Languagementioning
confidence: 99%